2011
DOI: 10.5194/cpd-7-1647-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Present and LGM permafrost from climate simulations: contribution of statistical downscaling

Abstract: We quantify the agreement between permafrost distributions from PMIP2 (Paleoclimate Modeling Intercomparison Project) climate models and permafrost data. We evaluate the ability of several climate models to represent permafrost and assess the inter-variation between them. <br><br> Studying an heterogeneous variable such as permafrost implies to conduct analysis at a smaller spatial scale compared with climate models resolution. Our approach consists in applying statistical downscaling methods (SDMs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…This species has particularly low dispersal abilities, and populations separated by only a few kilometres are significantly differentiated (Ursenbacher et al 2009). The common adder is a cold-adapted species with a large boreal distribution (probably the largest for a terrestrial snake; Saint Girons 1980) reaching high latitude (>60°N) and the permafrost seems to limit its distribution (Nilson et al 2005;Levavasseur et al 2011). The range-wide mitochondrial DNA phylogeography of the adder indicated three major clades: one in the Balkan peninsula, one in the Italian peninsula and one with a large distribution from France to Sakhalin Island (Kalyabina-Hauf et al 2004;Ursenbacher et al 2006 Clark et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This species has particularly low dispersal abilities, and populations separated by only a few kilometres are significantly differentiated (Ursenbacher et al 2009). The common adder is a cold-adapted species with a large boreal distribution (probably the largest for a terrestrial snake; Saint Girons 1980) reaching high latitude (>60°N) and the permafrost seems to limit its distribution (Nilson et al 2005;Levavasseur et al 2011). The range-wide mitochondrial DNA phylogeography of the adder indicated three major clades: one in the Balkan peninsula, one in the Italian peninsula and one with a large distribution from France to Sakhalin Island (Kalyabina-Hauf et al 2004;Ursenbacher et al 2006 Clark et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…During MIS 2 (Late Pleniglacial, 27-15 ka) the temperatures decreased and arid conditions with strong winds prevailed (Bos et al 2001;Guiter et al 2003). The coldest period with polar desert conditions and scarce vegetation occurred c. 20 ka (Huijzer & Vandenberghe 1998;Guiter et al permafrost (Huijzer & Vandenberghe 1998), although modelling results of Levavasseur et al (2011) point to an absence of permafrost during the Last Glacial Maximum (LGM, c. 21 ka) in central Europe. The end of MIS 2 (Lateglacial, 15-12 ka) was characterized by alternating cold (arid) and warm (humid) periods, as indicated by pollen data and soil formation (Kasse 2002;Guiter et al 2003).…”
mentioning
confidence: 99%
“…In comparison, the role of soil depth is second to that of horizontal resolution in influencing the abilities of models. Previous air temperature-based studies indicated that the distribution of permafrost might be moderately refined in heterogeneous mountainous regions by improving the method of downscaling air temperature (Levavasseur et al 2011;Saito et al 2014). Levavasseur et al (2011), who investigated permafrost on the basis of the air temperatures obtained from the PMIP2 models, suggested that a sophisticatedly downscaled temperature field could reduce the biases in the Qilian, Tianshan and Altai mountains and on the Tibetan Plateau.…”
Section: Resultsmentioning
confidence: 99%
“…G-I are for annual thawing index (cumulative degree days above 0°C within a year; units:°C day). [Colour figure can be viewed at www.boreas.dk] air temperature-based permafrost was strongly dependent on large-scale air temperature at the surface (Levavasseur et al 2011). In other words, downscaling is limited by large-scale errors from climate models in the last glacial maximum period.…”
Section: Resultsmentioning
confidence: 99%